Merekonstruksi Merekonstruksi Nilai Toleransi Dalam Ruang Privat Politik: Kajian Fenomena Perundungan Rumah Di Kalangan Anggota DPR-RI Indonesia. - agustan; Fajrul Ilmy Darussalam; Andi Batara Indra; Sabaruddin (Ganesha Civic Education Journal, 2025)
This study examines the reconstruction of tolerance values ​​in the private political sphere through the phenomenon of domestic bullying among members of the Indonesian House of Representatives (DPR-RI) as a reflection of the moral crisis and the decline of public ethics in Indonesia. This study uses a descriptive qualitative approach based on analytical and interpretive literature reviews. This study combines Michel Foucault's theory of power, Pierre Bourdieu's theory of habitus, and Pancasila ethics to reveal how dominating relations in the public sphere spread to the domestic sphere and normalize authoritarian behavior among the political elite. The results of the study indicate that domestic bullying is not an individual problem, but rather a product of the reproduction of structural power and the weak internalization of just and civilized humanitarian values. Therefore, the reconstruction of tolerance values ​​demands a reform of humanistic and accountable political ethics through reflective moral-political education, improvements to the DPR-RI's ethical institutions, and strengthening social control of civil society to uphold a civilized, egalitarian political culture that is in line with the principles of Pancasila.